TAFSIR AND THE STATE: AN ANALYSIS OF THE VERSES OF STATEHOOD IN TAFSIR AL-QUR’ANUL KARIM NURUL HUDA - Maghfiratuzzahroh, Maghfiratuzzahroh (Sekolah Tinggi Agama Islam Sadra, 2024)
This article will analyze the relationship between tafsir and the state in Tafsir Madura, namely Tafsir Al-Qur’anul Karim Nurul Huda by Mudhar Tamim. Mudhar Tamim was one of the politicians during the New Order, so there may be a discourse related to the state. So, this article will try to see how the interpretation of verses about statehood and leadership in the Qur’an through a critical review of the interpretation of Q.S. Al-Baqarah [2]: 30, Q.S. Al-Baqarah [2]: 154, Q.S. Al-Baqarah [2]: 216, and Q.S. Al-Baqarah [2]: 247 as well as excerpts of explanations regarding the virtues of reading basmalah. Through these verses, it will be seen how the socio-political contestation that occurred during the New Order period affected Mudhar Tamim’s interpretation. This research is a literature study with an analytical-descriptive method using Karl Manheim’s sociology of knowledge theory. After looking at the interpretation of the verses mentioned above through Mannheim’s sociology of knowledge, it can be concluded that Mudhar Tamim’s interpretation seems very close to the condition of the Indonesian state at the time of writing, as evidenced by the verses of state defense which are related to the spirit of Indonesian independence and the verses of the caliph which are related to the state leader. However, Mudhar Tamim’s interpretation, especially in the leadership verses, criticizes and evaluates the government. So, it can be said that Mudhar Tamim’s tafsir Al-Qur’anul Karim Nurul Huda is a form of counter-discourse from the Soeharto regime.